Effect of Inoculum and of Beta-Lactamase on the Anti-Staphylococcal Activity of Thirteen Penicillins and Cephalosporins - Sabath, L. D. (1975)
Because there are few persuasive data for selecting one semisynthetic penicillin or cephalosporin over another for treatment of serious staphylococcal infections, 118 recent clinical isolates of Staphylococcus aureus were studied to determine to what extent the presence of β-lactamase affected the relative anti-staphylococcal activity of six penicillins and seven cephalosporins. In addition, the effect of inoculum was studied for its possible effect on the anti-staphylococcal activity of the 13 β-lactam antibiotics. By all criteria, methicillin and nafcillin were clearly more resistant to both the inoculum effect and the production of staphylococcal β-lactamase, whereas benzylpenicillin and cephaloridine (especially benzyl-penicillin) were the most susceptible to these effects. Cephazolin was clearly more susceptible to staphylococcal β-lactamase and heavy inocula than the other cephalosporins (with the exception of cephaloridine), whereas cephalothin was the most resistant cephalosporin to these factors. The minimal inhibitory concentration for benzylpenicillin for tests with undiluted inoculum, compared to results with inoculum diluted 10(−4), differed by a factor up to 16,384, whereas with methicillin and nafcillin the differences were rarely more than twofold. Ratios for the other 10 antibiotics fell between these extremes. These results suggest that methicillin or nafcillin is most stable to staphylococcal β-lactamase, and that benzylpenicillin and cephaloridine are the most susceptible.